Modeling of hysteresis loop and its applications in ferroelectric materials. Issue 4 (March 2018) - Ma, Zhi; Ma, Yanan; Chen, Zhipeng; Zheng, Fu; Gao, Hua; Liu, Hongfei; Chen, Huanming
Abstract: In order to understand the hysteresis loop of ferroelectric materials, we deduced a novel model combined with the electric field, the temperature and the stress as a united parameter for describing the diversified hysteresis loops. This model indicated that the hysteresis loop of ferroelectric materials can be determined by the saturation of polarization, the coercive field and the electric susceptibility as well as the equivalent energy field analytically. For validation, the retraced relationship among the polarization, the applied electric field and the environmental temperature by our proposed model has been compared with the experimental data extracted from reported literatures. As an application of this model, the formula of energy storage efficiency, the formula of electrocaloric effect and the analytical formula of polarization as a function of the applied electric field, the temperature and the stress have also been investigated in this article.